Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Kantor Dinas Pemberdayaan Masyarakat Dan Desa (Dpmd) Provinsi Bengkulu - Epa Dui Rahayu; Ida Ayu Made Er Meytha Gayatri; Yesi Indian Ariska (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Employee performance is the quality and number of individual consequences or combinations in exclusive actions caused by the characteristic capacity obtained from learning interactions and to perform better.The purpose of the study was to determine the effect of work discipline on employee performance at the Bengkulu Province Community and Village Empowerment Office (DPMD), to determine the effect of work motivation on employee performance at the Bengkulu Province Community and Village Empowerment Office (DPMD). This study aims to determine the effect of work discipline and work motivation on employee performance at the Bengkulu Province Office of Community and Village Empowerment (DPMD). The sample in this study was 44 employees, data collection using questionnaires and data analysis methods used multiple linear regression, determination test, and hypothesis testing.The results for the multiple regression equation show a positive regression direction with the equation Y = 8.747 + 0.797 (X1) + 0.732 (X2) + e, meaning that if there is an increase in work discipline and work motivation, the performance of employees in the community and village empowerment office (DPMD) Bengkulu Province will also increase. Work discipline has a significant effect on employee performance at the Bengkulu Province Community and Village Empowerment Office (DPMD) because the value shows the t count of 2,954 with a significant level of 0.003 < from 0.05. Work motivation has a significant influence on employee performance at the Bengkulu Province Community and Village Empowerment Office (DPMD) because it shows a t count of 2.525 > t table with a significant level of 0.012 < from 0.050. The test results conclude that there is a significant influence between work discipline and motivation on employee performance at the Bengkulu Province Community and Village Empowerment Office (DPMD) together because the F arithmetic value > F table (152,915 > 3,133) with a significant value of 0.000 < 0.05.